2008
DOI: 10.1007/bf03191113
|View full text |Cite
|
Sign up to set email alerts
|

Effects of verapamil on etoposide pharmacokinetics after intravenous and oral administration in rats

Abstract: Etoposide is mainly metabolized by cytochrome P450 (CYP) 3A and is a substrate for P-glycoprotein (P-gp). This study examined the effects of verapamil, a CYP3A and P-gp inhibitor, on the pharmacokinetics of etoposide in rats. A single dose of etoposide was administered via oral (p.o.; 10 mg/kg) or intravenous (i.v.; 3.3 mg/kg) routes to rats alone (control animals) or together in combination with verapamil (2 or 6 mg/kg; experimental animals). The presence of verapamil significantly increased the area under th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 17 publications
(13 reference statements)
1
9
0
Order By: Relevance
“…A possible explanation to enhanced bioavailability of oral etoposide by these three aforementioned drugs could be due to an inhibition of CYP450-catalyzed metabolism and ABCB1-mediated efflux in the intestine and/or liver 75–77. Similar results were obtained with verapamil and PSC833 (valspodar), a CYP3A and ABCB1 inhibitor 40,78,79…”
Section: Bioavailability Of Oral Etoposidesupporting
confidence: 77%
“…A possible explanation to enhanced bioavailability of oral etoposide by these three aforementioned drugs could be due to an inhibition of CYP450-catalyzed metabolism and ABCB1-mediated efflux in the intestine and/or liver 75–77. Similar results were obtained with verapamil and PSC833 (valspodar), a CYP3A and ABCB1 inhibitor 40,78,79…”
Section: Bioavailability Of Oral Etoposidesupporting
confidence: 77%
“…However etoposide has shortcomings of low and variable bioavailability after oral dosing [9,10]. Currently different pharmacological approaches are being explored in order to demonstrate any potentially useful improvement in rate and extent of etoposide absorption into the systemic circulation in the clinical setting of oral therapy [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, inhibitors of P-gp may increase the oral absorption of drugs transported by P-gp. For example, verapamil enhanced bioavaibility of etoposide in rats [14]. In vitro study using human intestinal cell line (Caco-2) has shown that everolimus is a potent substrate for P-gp-like mediated efflux and this efflux was completely inhibited by verapamil.…”
Section: -Introductionmentioning
confidence: 99%